E2F1 copy number variations in germline and breast cancer: a retrospective study of 222 Italian women - Maria Santa Rocca; Clara Benna; Elena Goldin; Andrea Di Nisio; Luca De Toni; Ilaria Cosci; Alberto Marchet; Donato Nitti; Carlo Foresta (BMC, 2021)
Abstract Background Breast cancer is the most common neoplasia among women in developed countries. The risk factors of breast cancer can be distinguished in modifiable and unmodifiable factors and, among the latter, genetic factors play a key role. Copy number variations (CNVs) are genetic variants that are classified as rare when present in less than 1% of the healthy population. Since rare CNVs are often cause of diseases, over the last years, their contribution in carcinogenesis has become a relevant matter of study. E2F1 is a transcriptional factor that plays an important role in regulating cell cycle and apoptosis. Its double and conflicting role is the reason why it acts both as oncogene and as tumour suppressor, depending on cell context. Since anomalies in expression or in number of copies of E2F1 have been related to several cancers, we aimed to study number of germline copies of E2F1 in women with breast cancer in order to better elucidate their contribution as predisposing factor to this tumour. Methods We performed, hence, a retrospective study on 222 Italian women with breast cancer recruited from October 2002 to December 2007. TaqMan CNV assay and Real-Time PCR were carried out to analyse, respectively, E2F1 CNV and E2F1 expression in the subjects of the study. Chi square test or Fisher's exact test and Student's t‐test were used to calculate the frequency of CNVs and differences in continuous variables between groups, respectively. Results Intriguingly, we found that 10/222 (4.5%) women with breast cancer had more copies than controls (0/200, 0%), furthermore, the number of copies positively correlated with E2F1 gene expression in breast cancer tissue, suggesting that the constitutive gain of the gene could translate into an increased risk of genomic instability. Additionally, we found that altered E2F1 copies were present prevalently in the patients with contralateral breast cancer (20%) and all of them had a positive family history, both typically associated with hereditary cancer. Conclusions Our findings suggest that copy number variations of E2F1 might be a susceptibility factor for breast cancer, however, further studies on large cohorts are to be performed in order to better delineate the phenotype linked to the gain of E2F1 copies.